Vloga lektorja v opernem gledališču - Filipčič Redžić, Marja (Jezik in slovstvo, 2019)
In opera theatres, a speech consultant assists singers in pronouncing foreign languages, as well as helping them with the pronunciation of Slovenian. A sung opera text needs to be intelligible and linguistically standardised. The articulation of the sounds of Slovenian literary language in opera singing depends on the linguistic norm and on musical laws. The opera theatre speech consultant is involved in the process of creating a performance from the very beginning. Detailed knowledge of the text, as well as of music and directing concepts, also enables the consultant to proofread the texts in the theatre programme in a quality way and to ensure that the surtitles correspond to the stage action.
Keywords: gledališki lektor; jezikovna norma; operno gledališče; pravorečje; slovenščina